Multiple layers: The Aga Khan Museum and Complex (American Journal of Islam and Society, 2015)
To appreciate North York’s newly opened Aga Khan Museum (AKM), onemust first understand its patron, as this undertaking is only the most recent ina long line of proactive institutions and projects initiated by the Aga Khan allover the world. The Aga Khan and members of his family have cultivated thiscollection for decades, and have given it a permanent home in North York. Infact, this striking building located within a complex of the Ismaili Center andgardens, is the first North American museum dedicated exclusively to Islamicarts and culture.